2022
DOI: 10.1039/d2en00435f
|View full text |Cite
|
Sign up to set email alerts
|

Carbon dots derived from natural sources and their biological and environmental impacts

Abstract: Carbon dots (CDs) have successfully stood out among numerous materials, attributed to their superior characteristics, including ultra-small size, good photostability, excellent biocompatibility, and tunable fluorescent property. Accompanied with their remarkable...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 137 publications
(194 reference statements)
0
9
0
Order By: Relevance
“…This method offers a self-passivated one-step synthesis process, easy heteroatom doping, cost-efficiency, non-toxicity, and highly efficient synthesis. 67,78,79 However, in some cases, time-consuming reactions and low quantum yield (QY) are the main concerns of this method. In the pyrolysis method, the CDs are synthesized by carbonization or pyrolysis of carbon sources at a higher temperature.…”
Section: Green Synthesis Of Carbon Dotsmentioning
confidence: 99%
See 1 more Smart Citation
“…This method offers a self-passivated one-step synthesis process, easy heteroatom doping, cost-efficiency, non-toxicity, and highly efficient synthesis. 67,78,79 However, in some cases, time-consuming reactions and low quantum yield (QY) are the main concerns of this method. In the pyrolysis method, the CDs are synthesized by carbonization or pyrolysis of carbon sources at a higher temperature.…”
Section: Green Synthesis Of Carbon Dotsmentioning
confidence: 99%
“…Additionally, the adjustment of synthesis conditions such as the heating rate, reaction temperature, and duration benefits the synthesis of desired CDs. 67,77,78,[80][81][82] In Table S1, † the CDs are synthesized via a bottom-up approach using carbon precursors such as plant extract, fruit pulp, peel, and agricultural waste are listed. We also compared the advantages and disadvantages of this approach to top-down and on this basis, we elucidate the advantages of green CDs over other methods and carbon sources (Table S2 †).…”
Section: Green Synthesis Of Carbon Dotsmentioning
confidence: 99%
“…On one hand, carbon sources for the synthesis of carbon dots are very rich, ranging from organic molecules to flowers, trees, fruits, vegetables, grains, animal hair, eggs, milk, and so on. [ 77,79‐82 ] These raw materials for the synthesis of CDs with high fluorescence quantum yield are cheap and nontoxic, which benefit the large‐scale preparation for feeding silkworms. [ 83‐86 ] On the other hand, the properties of CDs are easily adjustable.…”
Section: Fluorescent Materialsmentioning
confidence: 99%
“…However, the pollution and waste also reside in the reported chemical routes to synthesize the highly efficient deep-red/NIR emissive CNDs. Recently, several researchers reported that the biomass can be utilized as the recyclable raw precursor to prepare CNDs via carbonization or direct extraction, enabling further applications as the bright deep-red emissive phosphor or bioimaging agents. , These biomass-derived CNDs or composites harbor the potential biological applications of versatile CND-based nanomaterials. Hence, it is significant to develop a new safe and pollution-free approach to recycling CNDs from widespread biomass.…”
Section: Introductionmentioning
confidence: 99%